Development of poly(vinyl alcohol)/chitosan/aloe vera gel electrospun composite nanofibers as a novel sorbent for thin-film micro-extraction of pesticides in water and food samples followed by HPLC-UV analysis. (17th January 2022) - Hejabri Kandeh, Saeed; Amini, Shima; Ebrahimzadeh, Homeira
Abstract : Schematic presentation of applying PVA/CA/CS/AV composite nanofibers as the extraction phase in thin-film micro-extraction (TFME) of six pesticide compounds prior to HPLC-UV analysis. Abstract : Herein, a novel composite of poly(vinyl alcohol) (PVA)/citric acid (CA)/chitosan (CS)/aloe vera gel (AV) was fabricated via the electrospinning technique followed by a thermal treatment. The resultant composite was characterized, and then applied as the sorbent for thin-film micro-extraction (TFME) of six pesticide compounds prior to HPLC-UV analysis. Various factors affecting the extraction performance were evaluated and optimized. Under optimal conditions, the detection limits (at S/N ratio of 3) and the limits of quantification (at S/N ratio of 10) were calculated to be 0.2–0.5 ng mL −1 and 0.6–1.5 ng mL −1, respectively. The linearity was in the range of 0.6 to 600.0 ng mL −1 with correlation coefficients of ≥0.9977. The relative standard deviations (RSDs) were achieved in the range of 4.7–5.9% (intra-day, n = 5) and 5.6–6.9% (inter-day, n = 3) for three consecutive days. Ultimately, the capability of the method was appraised for the simultaneous monitoring of pesticides in water and food samples with acceptable recoveries (86.3 to 96.8%).